Teaching a Systems Approach to Manage Smart Sustainable Cities - Zhu, Quan; Haveman, Steven (39th Bled eConference: Co-Creating Human-Centred and Responsible Digital Futures; Conference Proceedings, 2026)
Cities are pushing their boundaries to transform into smart and sustainable urban spaces, where factors such as ecological conservation, economic development, and democratic equity should be considered at the same time. Systems thinking is therefore among the most needed skills for practitioners managing smart sustainable cities. The purpose of this paper is to initiate the development of a curriculum for a systems approach to manage smart sustainable cities, leveraging theoretical concepts of systems thinking. Our framework will enable learners to view societal challenges as outcomes of social-ecological system behaviour over time, so that key leverage points for interventions can be identified.